2023
DOI: 10.1136/bmjmed-2022-000385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of covid-19 vaccination on long covid: systematic review

Abstract: ObjectiveTo determine the effect of covid-19 vaccination, given before and after acute infection with the SARS-CoV-2 virus, or after a diagnosis of long covid, on the rates and symptoms of long covid.DesignSystematic review.Data sourcesPubMed, Embase, and Cochrane covid-19 trials, and Europe PubMed Central (Europe PMC) for preprints, from 1 January 2020 to 3 August 2022.Eligibility criteria for selecting studiesTrials, cohort studies, and case-control studies reporting on patients with long covid and symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 44 publications
5
62
0
Order By: Relevance
“…A systematic review of 16 observational studies from five countries also published in BMJ Medicine this week similarly concluded that covid-19 vaccines could both protect against and help to treat long covid 3…”
Section: Growing Evidencementioning
confidence: 99%
“…A systematic review of 16 observational studies from five countries also published in BMJ Medicine this week similarly concluded that covid-19 vaccines could both protect against and help to treat long covid 3…”
Section: Growing Evidencementioning
confidence: 99%
“…Concepts such as "radical rest" or "pacing" have entered the long COVID conversation as both a preventative and restorative concept to allow for ample healing and prevent symptom exacerbations, regardless of the presence of post-exertional malaise [6]. These techniques should be considered in conjunction with mRNA-based COVID-19 vaccination administration, which is believed to be both preventative and therapeutic in the long COVID setting [7]. Thereafter lies utility in treating secondary illness that may have been exacerbated by SARS-CoV-2 infection or associated deconditioning and encouraging a variety of lifestyle changes to adapt to this otherwise chronic illness.…”
Section: Figure 1: a Subjective Visualization Of The Perceived Phases...mentioning
confidence: 99%
“…Protection from vaccination alone is thought to be somewhere between 15%-50% [51]. A recent systematic review reported great uncertainty in the scale but likely definite benefit of vaccination in preventing Long Covid [52]. Assuming hybrid protection is better than vaccination alone, we choose a range of 30%-70% Overall effectiveness of previous infection 1 year earlier against new Long Covid on reinfection.…”
Section: %-78%mentioning
confidence: 99%